An ism approach for managing critical stakeholder issues regarding carbon capture and storage (Ccs) deployment in developing asian countries - Abdullah, M.R.T.L. (MDPI AG, 2021)
Carbon capture and storage (CCS) technology deployment in developing Asian countries largely depends on public acceptance, which is highly dependent on the stakeholders involved in CCS. This paper illuminates how stakeholder issues could be strategically managed in the deployment of CCS, in a manner customized to such developing countries. Based on the input from 28 stakeholders of various interests and nationalities (i.e., from China, Malaysia, Thailand, Vietnam, the Philippines, and Indonesia), this study applies Interpretive Structural Modeling (ISM) and MICMAC analysis, in order to develop a management model to address stakeholder issues regarding the deployment of CCS. Our findings revealed eight legislative issues, four social issues, three economic issues, five technological issues, and five environmental management issues. The model revealed that legislative issues, such as those relating to CO2 definition, licensing, land acquisition framework, and expertise, should be managed prior to other issues, that is, in the early stage of CCS deployment. Addressing environmental issues related to promoting public awareness and perception of CCS benefits are among the key drivers in deploying CCS. The study may serve as a reference for CCS deployment in developing Asian countries. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.